PENGARUH KOMPETENSI DAN MOTIVASI TERHADAP KINERJA GURU DENGAN LINGKUNGAN KERJA DAN KEPEMIMPINAN KEPALA SEKOLAH SEBAGAI VARIABEL MODERASI - UNTUNG SUNARDI, 11.52.02.0079 (Jurnal Mahasiswa Pasca Sarjana, 2014)
The purpose of riset to examine âInfluence competensi and motivasi to performance of teachers by work environment and management headmaster as variabel moderasi. The example of riset are 130 persons . The way to take the example by purposive proporsional random sampling. The way of analysis data by using : validitas test with analysis factor, reliabilitas test, by Alpha Chrombach, model test by Adjusted R2 and test F, hipotesis test by MRA test and test t. The result of the riset show that : 1. Competensi have positive influence and significan to performance of teachers. 2. The motivasi is not influence to performance of teachers. 3. The work environment have positive influence and significan toÂ  performance of teachers. 4. The management of headmaster is not influence to performance of teachers. 5. The work environment can not guide to the relation between competensi and performance of teachers.6. The work environment can be guide the relation between competensi and performance of teachers.7. The managament of headmaster is not be guide the relation between motivasi and performance of teachers. The summarize of this riset is to increase performance of civil servant teachers Senior High School regency Pati. It can be work by : increase competensi and motivasi performance of teachers. It is support by work environment and managament of headmaster. Key word : competensi, work motivasi, performance, work environment and management of headmaster